A Convenient Method for the Preparation of 4,10-Dinitro-2,6,8,12-tetraoxa-4,10-diazatetracyclo[5.5.0.05,903,11]dodecane via Nitration of 1,4-Diformyl-2,3,5,6-tetrahydroxypiperazine Using [Msim]NO3 - Ghaderi, Hossein; Zolfigol, Mohammad Ali; Bayat, Yadollah; Zarei, Mahmoud; Noroozizadeh, Ehsan (Synlett, 2016)
Improvement of methods for the synthesis of high-energetic scaffolds such as 4,10-dinitro-2,6,8,12-tetraoxa-4,10-diazaisowurtzitane or 4,10-dinitro-2,6,8,12-tetraoxa-4,10-diazatetracyclo [5.5.0.05,903,11]dodecane (TEX) is in demand because these materials may be used as high explosives. Herein, we demonstrate that the ionic liquid 3-methyl-1-sulfonic acid imidazolium nitrate ([Msim]NO3) is an efficient reagent for the synthesis of TEX via nitration of 1,4-diformyl-2,3,5,6-tetrahydroxypiperazine (DFTHP) with high efficiency and short reaction time and under mild conditions.
Keywords: TEX; DFTHP; [Msim]NO3; 1,4-diformyl-2,3,5,6-tetrahydroxypiperazine